THE DISTRIBUTION AND POTENTIAL PROBLEMS OF MIMOSA PIGRA L. IN INDONESIA - TJITROSOEDIRDJO, SRI S. (SEAMEO BIOTROP, 1989)
Mimosa pigra L. (Mimosa asperata L.) of the family Mimosaceae is an introduced species from South America which is locally naturalized in Indonesia. The present known distribution sites are still restricted to Java, Sumatra, and Kalimantan. It is found in almost all provinces of Java and many heavily infested areas have been noted in Jakarta and West Java. The introduction of the plant to other islands has not been reported yet. The separation of the islands by sea is preventing the further spread of the plant in Indonesia. Control is basically occasional and on an individual basis. There is no sustained effort yet to control the plant. The urgency of controlling and restricting its spread cannot be over emphasized.